Immobility responses between mouse strains correlate with distinct hippocampal serotonin transporter protein expression and function - Tang, Man; He, Tao; Meng, Qing-yan; Broussard, John Isaac; Yao, Lan; Diao, Yao; Sang, Xiu-bo; Liu, Qing-peng; Liao, Ying-jun; Li, Yuge; Zhao, Shulei (The international journal of neuropsychopharmacology, 2014)
Mouse strain differences in immobility and in sensitivity to antidepressants have been observed in the forced swimming test (FST) and the tail suspension test (TST). However, the neurotransmitter systems and neural substrates that contribute to these differences remain unknown. To investigate the role of the hippocampal serotonin transporter (5-HTT), we measured baseline immobility and the immobility responses to fluoxetine (FLX) in the FST and the TST in male CD-1, C57BL/6, DBA and BALB/c mice. We observed strain differences in baseline immobility time, with CD-1 mice showing the longest and DBA mice showing the shortest. In contrast, DBA and BALB/c mice showed the highest sensitivity to FLX, whereas CD-1 and C57BL/6 mice showed the lowest sensitivity. Also we found strain differences in both the total 5-HTT protein level and the membrane-bound 5-HTT level (estimated by Vmax) as follows: DBA > BALB/c > CD-1 = C57BL/6. The uptake efficiency of the membrane-bound 5-HTT (estimated by 1/Km) was highest in DBA and BALB/c mice and lowest in CD-1 and C57BL/6 mice. A correlation analysis of subregions within the hippocampus revealed that immobility time was negatively correlated with Vmax and positively correlated with Km in the hippocampus. Therefore a higher uptake capacity of the membrane-bound 5-HTT in the hippocampus was associated with lower baseline immobility and greater sensitivity to FLX. These results suggest that alterations in hippocampal 5-HTT activity may contribute to mouse strain differences in the FST and the TST.